Edukasi Pencegahan Anemia melalui Peningkatan Pemahaman Remaja mengenai Peran Hemoglobin di SMK Negeri 10 Garut - Lia Mar’atiningsih; Meti Rizki Utari (Compromise Journal Community Proffesional Service Journal, 2025)
Anemia is a global health problem with a high prevalence among adolescents, especially girls, due to increased iron requirements, rapid growth, and menstruation. This condition impacts health, concentration, and quality of life. Hemoglobin, as an indicator of anemia, plays a crucial role in oxygen transport, so adolescents' understanding of its function is crucial. This activity aims to increase adolescents' understanding of the role of hemoglobin and anemia prevention through health education at SMK Negeri 10 Garut. The method used was a participatory approach through an initial questionnaire, material delivery, discussion, and post-education evaluation. The results showed an increase in students' knowledge about anemia and hemoglobin. This education effectively increases adolescents' awareness and motivation to improve their diets, so it needs to be implemented continuously with the support of schools, parents, and health workers.